A Survey on Socially Assistive Robotics: Clinicians’ and Patients’ Perception of a Social Robot within Gait Rehabilitation Therapies - Raigoso, Denniss; Céspedes, Nathalia; Cifuentes, Carlos A.; del Ama, Antonio J; Múnera, Marcela (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
A growing interest in Socially Assistive Robotics in Physical Rehabilitation is currently observed; some of the benefits highlight the capability of a social robot to support and assist rehabilitation procedures. This paper presents a perception study that aimed to evaluate clinicians’ and patients’ perception of a social robot that will be integrated as part of Lokomat therapy. A total of 88 participants were surveyed, employing an online questionnaire based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The participants belong to two health care institutions located in different countries (Colombia and Spain). The results showed an overall positive perception of the social robot (>60% of participants have a positive acceptance). Furthermore, a difference depending on the nature of the user (clinician vs. patient) was found.

Actualmente se observa un creciente interés en la Robótica de Asistencia Social en la Rehabilitación Física; algunos de los beneficios resaltan la capacidad de un robot social para apoyar y asistir en los procedimientos de rehabilitación. Este artículo presenta un estudio de percepción que tuvo como objetivo evaluar la percepción de los médicos y los pacientes sobre un robot social que se integrará como parte de la terapia Lokomat. Se encuestó a un total de 88 participantes, empleando un cuestionario en línea basado en la Teoría Unificada de Aceptación y Uso de la Tecnología (UTAUT). Los participantes pertenecen a dos instituciones de atención médica ubicadas en diferentes países (Colombia y España). Los resultados mostraron una percepción general positiva del robot social (>60% de los participantes tienen una aceptación positiva). Además, se encontró una diferencia según la naturaleza del usuario (médico vs. paciente)
Keywords: Rehabilitación médica; Medical rehabilitation; Tecnología médica; Medical technology; Robótica médica; Robotics in medicine; Terapia Lokomat; Lokomat therapy; Social robots; Robots sociales; Physical rehabilitation; Rehabilitación física; Perception; Percepción; Gait rehabilitation; Rehabilitación de la marcha; Lokomat